The European Light Dosimeter Network: four years of measurements - Lebert, Michael; Schuster, Martin; Häder, Donat-Peter (Journal of Photochemistry and Photobiology B-Biology, 2002)
The European Light Dosimeter Network (ELDONET) has now been functional for more than four years. The network is based on dosimeters which measure radiation in three biologically relevant wavelength bands (UV-B, 280-315 nm; UV-A, 315-400 nm; and Photosynthetic Active Radiation, PAR, 400-700 nm). The ELDONET network is currently based on 33 stations with 40 instruments. The distribution of the instruments all over Europe allows measurement of the latitudinal and longitudinal light climate distribution. In addition, several instruments are active in South America, New Zealand, India, Africa and Japan. With some exceptions, the measured yearly doses depend on the latitude. While the maximal daily doses are almost comparable from station to station, seasonal changes and the different maximal solar zenith angles account for the differences in total yearly doses. Ratioing between UV-B and PAR allows the detection of subtle changes in the local light climate, due, for example, to mini-ozone holes encountered in northern Europe during spring. Comparison of satellite ozone data with terrestrial ELDONET measurements revealed an overall weak correlation between these data sets. However, local weather conditions, solar zenith angle and latitude as well as reflectivity (i.e. clouds and aerosol; satellite data) show a much stronger correlation to the doses received. The close relationship between the spectral sensitivity of the UV-B sensor used in the ELDONET dosimeter and the CIE erythemal action spectrum allows determination of the erythemal dose on the basis of the dosimeter readings. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: European light climate; erythemal dose; photosynthetic active radiation (PAR); solar radiation; UV-A; UV-B